Fantasy Literature and Lyric Discourse. Characterisation and Analysis of Current Spanish Fantasy Poetry - Ema Llorente, María (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This paper supports the possibility of including lyric poetry within the manifestations of the fantastic, which is usually limited or confined to the narrative genre. For this purpose, a review of the assumptions supported in the main existing theoretical studies on this subject is carried out first. Also, the definition of fantasy as a literary genre provided by such studies as well as their arguments for its exclusion - the eminently subjective or emotional character of lyric poetry, its lack of external references and its unfitness for fiction or for a fictional approach, as well as its indirect and figurative language - are questioned. Following this review, some features - both thematic and formal - that can be used to characterise the lyric-fantastic discourse are proposed and specific cases of recent Spanish poetry that could fall within this definition are analysed.
Keywords: Literary genre, fiction, external reference, figurative language, enunciation.